1978
DOI: 10.1042/bj1750813
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and regulation of the myofibrillar adenosine triphosphatase

Abstract: 1. The steady-state kinetic behaviour of the ATPase (adenosine triphosphatase) of intact myofibrils was studied in the presence of both high and low concentrations of Ca2+ (0.25 mM and less than 10 nM respectively). 2. Kinetic data were collected over the initial linear phase of the assay, which lasts for 20--60s. To obtain consistent data we found it necessary to use either fresh myofibril preparations or preparations that had been stored in the presence of thiol compounds. 3. When assayed in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The source of the increased base-line tension at low ionic strength was not determined. In this regard, Goodno, Wall & Perry (1978) found that the ATPase activity of relaxed myofibrils increased as the ionic strength was reduced below physiological levels. This suggests that the increase in resting tension at an ionic strength of 0 09 M may result from cyclic interactions of cross-bridges with actin sites.…”
Section: Resultsmentioning
confidence: 98%
“…The source of the increased base-line tension at low ionic strength was not determined. In this regard, Goodno, Wall & Perry (1978) found that the ATPase activity of relaxed myofibrils increased as the ionic strength was reduced below physiological levels. This suggests that the increase in resting tension at an ionic strength of 0 09 M may result from cyclic interactions of cross-bridges with actin sites.…”
Section: Resultsmentioning
confidence: 98%
“…3) in reversible association with actin also increases (Stein et al, 1979) . Because k2 includes the refractory state transition, which is believed to be rate limiting in isolated protein systems (Eisenberg and Greene, 1980), and because the rate of hydrolysis increases in myofibrils with a decrease in ionic strength (over the range 0.1-0.2; Goodno et al, 1978), we argue that reduction in ionic strength decreases the lifetime of the refractory state, i.e., increases k2 . This will produce the effects we observe (Table II) : a left shift in the pCa/tension curve (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…When ionic strength is reduced, the hydrolysis rate of myofibrils increases (Goodno et al ., 1978) . The fraction of myosin products (X in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…ES is myosin ATPase, and the low rate of ATP formation gives a plausible first order kinetic for this enzyme. The first order kinetic constant kz = V$TPase/K~Tpase may be estimated to be 0.09 min-' for the myofilaments used in fig.2 (eTPase = 1.3 pM.min-'* KiTPase = 14pM [13]). v/a = 10 cm (v = 2 m;, volume of the spec- Fig.3.…”
Section: Creatine Kinase Activitymentioning
confidence: 99%